Implementation of a Microcontroller Arduino for Portable Peak Expiratory Flow Rate to Examine the Lung Health - Nabilla Farikha Azzahra; Priyambada Cahya Nugraha; Torib Hamzah; Kamilu O. Lawal (International Journal of Advanced Health Science and Technology, 2022)
A peak flow meter will measure the ability to push air out of the lungs; the lungs are one of the body's most vital organs. The commonly used method is to deploy a peak flow meter, which uses mechanical systems. This mechanical system is prone to a high error rate of reading, and as a result, a more accurate and reliable means becomes inevitable. This paper describes the design and implementation of a micro-controller-based portable peak flow meter, which can be used to provide accurate data for the diagnosis of asthma, bronchitis, and emphysema. In the heart of the system are the programmable Mega Arduino microcontroller and a device called MPX5100GP sensor, which has a pressure range of 0-100 Kpa to detect a patient breath. The device was equipped with a display facility, which uses Nextion touch TFT output to display related tests and examinations. There is also a provision to store the results data using SD Card, while a printer prints the test results for further diagnostic purposes. An experimental setup in the laboratory shows that the designed micro-controller-based PFM shows that the error rate was between 0.50 % and 4.21 % compared with the mechanical-based peak flow meter. The application of micro-controller-based peak flow meters also allows real-time and remote monitoring of peak flow parameters. The evolution of modern technology has made the possibility of developing a micro-controller based portable, peak flow meters, which can be used to measure the data involved in the diagnosis of lung-related diseases more accurately.